Outcomes of Perilunate Dislocation and Perilunate Fracture Dislocation After a Minimum 1-Year Follow-Up Following Open Reduction and Internal Fixation Via the Dorsal Approach: A Retrospective Study - Muennoi, Phanumas; Sangkomkamhang, Thananit (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: This study aimed to review and evaluate the functional and radiographic outcomes of patients with perilunate injuries after a minimum 1-year follow-up following open reduction and internal fixation with or without ligament repair. Methods: This retrospective study included patients with perilunate injuries who underwent open reduction and internal fixation with or without ligament repair at our hospital between 2013 and 2021 with a minimum 1-year follow-up. Results: Of the 22 enrolled patients, 18 and 4 exhibited perilunate fracture dislocation and perilunate dislocation, respectively. The mean follow-up period was 15.3 (12–20) months. The mean age of the patients was 30.5 ± 10.2 years. Notably, 20 (90.9%) and 2 (9.1%) patients were males and females, respectively. The mean flexion/extension angles were 67.2°/76.2°. The mean ulnar deviation/radial deviation was 25.4°/13.8°, and the mean pronation/supination was 85.6°/88.3°. As secondary outcomes, the mean grip strength was 80% of the uninjured side, modified Mayo wrist score was 73.6 (1 excellent, 6 good, 11 fair, and 4 poor), and visual analog scale was 0.59. For radiographic outcomes, the mean scapholunate angle (SL angle) was 50.4°, SL gap was 2.43 mm., and carpal height ratio was 0.50. Four and nine patients had an incongruent Gilula's line and arthrosis, respectively. Conclusions: Satisfactory results can be achieved with open reduction and internal fixation using a dorsal approach. Although some patients had abnormal radiographic findings, the radiographic outcomes may not correlate with the functional outcomes.